Hadith Content About Women on Instagram: Analysis of Religious Account Strategies to Attract Followers - Bakar, Abu; Manik, Zulfirman (Al-Fikru: Jurnal Ilmiah, 2024)
The social media platform Instagram has become a popular platform for religious accounts to proselytize. One strategy that is often used is posting hadith content that discusses women. This study aims to analyze how hadith content about women is used by religious accounts on Instagram as a strategy to hunt followers. This research uses qualitative methods with content analysis techniques. The results show that the content of hadith about women on Instagram succeeds in attracting audiences through attractive visuals and religious messages that are simple and easy to understand. However, some hadith content tends to be oversimplified or delivered without in-depth context, which can lead to misunderstandings among followers. While these accounts create high engagement and are effective in attracting new followers, there is a need to improve the accuracy and depth of the da'wah messages delivered. The strategy of hunting followers by utilizing hadith about women is successful, but attention to the accuracy of the hadith source and the presentation of a more comprehensive context is needed. This is important to ensure that proselytizing on social media is not only popularity-oriented, but also capable of providing in-depth and beneficial religious understanding on an ongoing basis.